Modern challenges to Islamic law - Ali, Shaheen Sardar (Law in context, 2016)
Engaging with topics as diverse as Islamic constitutionalism, Islamic finance, human rights and internet fatawa, Shaheen Sardar Ali provides an invaluable resource for scholars, students and practitioners alike by exploring exactly constitutes Islamic law in the contemporary world. Useful examples, case studies, a glossary of terms and the author's personal reflections accompany traditional academic critique, and together offer the reader a unique and discerning discussion of Islamic law in practice.